2023
DOI: 10.1161/strokeaha.122.039173
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Gender Differences in Leadership of Stroke-Related Clinical Trials

Abstract: BACKGROUND: Gender disparities among principal investigators of clinical trials (CT) can have implications regarding the areas of investigation, methods, conduct, trial enrollment, and interpretation of results. An estimation of the gender gap in the leadership of stroke-related CTs from North America has to date not been undertaken. METHODS: We extracted information about stroke-related CTs between 2011 and 2020 from www.Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Women's leadership in clinical trials has increased from 13% in 2007 to 22% in 2022. This growth is comparable to the representation of women as leaders in clinical trials across various medical specialties [16,18,23,34]. For instance, one study found an increase in women's leadership of oncology clinical trials from 17.5% in 1999 to 30.6% in 2019, suggesting an average annual growth of 0.65% [34].…”
Section: Proportion Of Women Principal Investigators Over Timementioning
confidence: 83%
“…Women's leadership in clinical trials has increased from 13% in 2007 to 22% in 2022. This growth is comparable to the representation of women as leaders in clinical trials across various medical specialties [16,18,23,34]. For instance, one study found an increase in women's leadership of oncology clinical trials from 17.5% in 1999 to 30.6% in 2019, suggesting an average annual growth of 0.65% [34].…”
Section: Proportion Of Women Principal Investigators Over Timementioning
confidence: 83%
“…The numbers in the study by Rawlley et al 8 deliver a clear message. We have failed in attracting and supporting young female medical doctors, not only in becoming clinical trialists and future academic leads, but first and foremost in specializing in stroke medicine.…”
mentioning
confidence: 94%
“…In this issue of Stroke , Rawlley et al 8 have revealed that academic gender inequity is only the tip of the iceberg in stroke medicine. They present the results of their retrospective analysis with estimation of the sex gap in the field of stroke trials in North America.…”
mentioning
confidence: 99%